KATA-KATA PINJAMAN BAHASA INGGRIS DALAM BAHASA INDONESIA PADA KORAN HARIAN â€œKOMENTAR MANADOâ€ - TAMBURIAN, NATANIA MEGIE; PAMANTUNG, RINA P.; SENDUK, ARTER JODI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research entitled â€œKata-Kata Pinjaman Bahasa Inggris dalam Bahasa Indonesia pada Koran Harian Komentar Manadoâ€.The objectives of this research are to find out the kinds and the changes of the meanings of English loan words in Indonesian language. In analyzing the data, the writer uses Haugenâ€™s theory to find out the types and Baughâ€™s theory to get the changes of the meanings.The result of research shows are three kinds of loan word. Those are loan word without phonemic substitution, loan word with partial phonemic substitution, loan word with complete phonemic substitution and theres three kinds of the changes of meaning such as extention and narrowing, but regeneration and degeneration process are not found in those loan words.It is excpected that the study will help student and readers in learning of sociolinguistic especially loanwords.Â Â Keywords: Loan Words, Change of Meaning, Socioliguistic, Komentar Manado Newspaper